ANALISIS SUMBER DAN PENGGUNAAN KAS PADA PT INDOCEMENT TUNGGAL PRAKARSA TBK - Mohammad Abdu; Martinus Robert Hutauruk; Mansyur (OBOR: Oikonomia Borneo, 2019)
The purpose of this study is to show the source and use of cash of PT Indocement Tunggal Prakarsa Tbk and can be used as a reference for assessing financial performance during the period 2017-2018. . By comparing the financial statements (balance sheet / statement of financial position) in 2017 compared to 2018 at PT. Indocement Tunggal Prakarsa Tbk. From the results of the analysis, it can be seen that the cash at PT. Indocement Tunggal Prakarsa Tbk experienced a decrease in 2018 amounting to Rp 1,069,015 Million from cash sources amounting to Rp 497,236 Million and Cash Used in the amount of Rp 1,566,251 Million. Keywords - Sources of Cash Receipts, Use of Cash,